Can Hearing Aids Delay Time to Diagnosis of Dementia, Depression, or Falls in Older Adults?. Issue 11 (4th September 2019) - Mahmoudi, Elham; Basu, Tanima; Langa, Kenneth; McKee, Michael M.; Zazove, Philip; Alexander, Neil; Kamdar, Neil
Abstract : OBJECTIVE: To examine the association between hearing aids (HAs) and time to diagnosis of Alzheimer disease (AD) or dementia, anxiety or depression, and injurious falls among adults, aged 66 years and older, within 3 years of hearing loss (HL) diagnosis. DESIGN: Retrospective cohort study. SETTING: We used 2008 to 2016 national longitudinal claims data (based on office visit, inpatient, or outpatient healthcare encounters) from a large private payer. We used Kaplan‐Meier curves to examine unadjusted disease‐free survival and crude and adjusted Cox regression models to examine associations between HAs and time to diagnosis of three age‐related/HL‐associated conditions within 3 years of HL diagnosis. All models were adjusted for age, sex, race/ethnicity, census divisions, and prior diagnosis of cardiovascular conditions, hypertension, hypercholesterolemia, obesity, and diabetes. PARTICIPANTS: The participants included 114 862 adults, aged 66 years and older, diagnosed with HL. MEASUREMENT: Diagnosis of (1) AD or dementia; (2) depression or anxiety; and (3) injurious falls. INTERVENTION: Use of HAs. RESULTS: Large sex and racial/ethnic differences exist in HA use. Approximately 11.3% of women vs 13.3% of men used HAs (95% confidence interval [CI] difference = −0.024 to −0.016). Approximately 13.6% of whites (95% CI = 0.13‐0.14) vs 9.8% of blacks (95% CI = 0.09‐0.11) and 6.5% of Hispanics (95% CI = 0.06‐0.07) used HAs. The risk‐adjusted hazard ratios of being diagnosed with AD/dementia, anxiety/depression, and injurious falls within 3 years after HL diagnosis, for those who used HAs vs those who did not, were 0.82 (95% CI = 0.76‐0.89), 0.89 (95% CI = 0.86‐0.93), and 0.87 (95% CI = 0.80‐0.95), respectively. CONCLUSIONS: Use of HAs is associated with delayed diagnosis of AD, dementia, depression, anxiety, and injurious falls among older adults with HL. Although we have shown an association between use of HAs and reduced risk of physical and mental decline, randomized trials are needed to determine whether, and to what extent, the relationship is causal. J Am Geriatr Soc 67:2362–2369, 2019